Balking blood pressure "control" by older persons of Bambuí, Minas Gerais State, Brazil: an ethno-epidemiological inquiry A resistência contra o "controle" da pressão arterial na população idosa de Bambuí, Minas Gerais, Brasil: um inquérito etno-epidemiológico - Marilyn Nations; Josélia O. A. Firmo; Maria Fernanda Lima-Costa; Elizabeth Uchôa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This ethno-epidemiological inquiry aims to comprehend hypertension-related experiences in the elderly population of Bambuí, in the State of Minas Gerais, Brazil. It combines ethnographic descriptions with statistical data. The subjective significance of factors associated with adequate arterial pressure control is explored. A baseline cohort of 26 people with hypertension, randomly selected from a total number of 1,494 residents over the age of 60, was interviewed utilizing signs, meanings and actions methodology. Multivariate analysis shows an association (p < 0.001) between female gender and monthly household income and treatment of hypertension and adequate blood pressure control. The number of doctor visits is associated with treatment but not with adequate blood pressure control. Conflicting cultural construction of "blood pressure problems" contributes to "non-adherence" to treatment. There is a fine line between blood pressure "control" and what is perceived as health professionals "controlling" patients' lives. Doctor-prescribed regimes are perceived as "prohibiting life's pleasures" and "controlling" personal liberty and free choice. Giving elderly people a voice regarding their social context can promote autonomy, well-being and happiness in later life. Esta pesquisa etno-epidemiológica objetiva compreender a experiência humana da hipertensão enquanto percebida por pessoas idosas em Bambuí, Minas Gerais, Brasil. Mescla descrições etnográficas com dados numéricos. Significados acerca dos fatores correlacionados ao controle da pressão arterial são aprofundados. De 1,494 residentes > 60 anos em uma base de coorte, 26 hipertensos idosos foram aleatoriamente selecionados e entrevistados utilizando signos, significados e ações. A análise multivariada associou (p < 0,001) o sexo feminino e renda mensal domiciliar ao tratamento da hipertensão mas não com controle da pressão adequado. Construções culturais conflitantes de "problema de pressão" contribuem para a "não-adesão" ao tratamento. Há uma tensão entre o "controle" da pressão arterial e os profissionais de saúde "controlando" a vida. "Regimes" prescritos pelos médicos proíbem os prazeres da vida, "controlando" a liberdade pessoal e o livre arbítrio. Dar voz aos idosos sobre suas condições sociais pode promover autonomia, bem estar e felicidade na últimas etapas da vida.